Profile and Operations of Highway Tourist Stop-over Foodservice Establishments in Uganda - Innocent Hope Tinka Mukama; Ivan Muzira Mukisa; Charles Kyeyune Muyanja (Centre For Tourism Planning and Development, 2023)
ABSTRACT This study was set out to identify and document the highway tourist stop-over foodservice establishments (HTSFE) characteristics; thus, creating a profile and grading for informed choice by tourists. The study adopted a cross-sectional design and quantitative data was collected from managers of establishments. The questionnaire was interviewer- administered in addition to an observational check-list. The study involved 30 HTSFE identified with the assistance from Uganda Tourism Board (UTB) and Uganda Safari Guides Association (USAGA). The response rate was 100%. Most of HTSFE were located in Western (47.6%) and Eastern Uganda (36.7%). Some were either stand-alone restaurants (40%) or part of a bigger hotel (43%). A considerable number (30%) employed between 1-5 food handlers and most (63.3%) had operated for more than 10 years. Majority (58.6%) were inspected by UTB in addition to either local council or city council. The commonest complaint recorded was delay in service (73.7%). The dishes prepared included local dishes (90%) and international cuisines (66.7%). Most HTSFE used water from National Water and Sewerage corporation (79.3%). None of the HTSFE had a food safety management system. The HTSFE belonged to three grade categories: B (36.6%), C (30%) and Non-graded (33.3%). The findings of the study suggest the need for implementing food safety management systems and more regular inspections and trainings for food safety assurance.